HUBUNGAN KELENGKAPAN SUMBER BELAJAR DENGAN HASIL BELAJAR EKONOMI PADA SISWA KELAS X SEMESTER GENAP SMA NEGERI 7 BANDAR LAMPUNG TAHUN PELAJARAN 2015/2016 - Arga, Kharisma Idola; Wahyudi, Tri; Handayani, Desi (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2016)
This study aims to determine the completeness of the relationship of learning resources with improved learning outcomes, and the degree of closeness of the relationship between the completeness of the learning resources with improved learning outcomes of economic subjects in class X second semester. The method used in this research is descriptive quantitative method. Where a population of 397 students. The sample in this study as many as 38 students were given a test in the form of 20 multiple-choice questions to determine student learning outcomes and questionnaires to determine the relationship of the completeness of the source of student learning. Testing the hypothesis in this study using product moment correlation test. Based on the results of hypothesis testing that has been done with the author, obtained = 0.645 greater than rdaf at the level of 5% with N = 38 is 0.320 (statistics table) this means. Namely 0.645> 0.320, which means that there is a relationship completeness of learning resources with the results of the economic study in grade x second semester.